Keadilan dalam kitab Amos: Suatu Tinjauan Ulang - Barus, Armand (Veritas : Jurnal Teologi dan Pelayanan, 2025)
Across time, humanity has cried out for justice in the face of injustice. In Indonesia, justice is also affirmed as a fundamental pillar of national life in the Preamble to the 1945 Constitution. Discussions of justice frequently turn to the book of Amos, yet they often concentrate primarily on social justice. This article reexamines justice in Amos through a dialogical reading of the book's literary context together with its historical, social, and religious contexts. The analysis argues that justice in Amos is multifaceted, encompassing distributive, retributive, restorative, theonomic, and mimetic dimensions. It further proposes that syncretism may be understood as a theological root of injustice because distorted relations with God are reflected in distorted human relations. Finally, the article brings Amos's vision of justice into dialogue with influential modern theories of justice in order to enrich contemporary reflection on the meaning and practice of justice.